Beyond Usual Care: A Multidisciplinary Approach Towards the Treatment of Obstructive Sleep Apnoea - Arachchige, Miuni Athauda; Steier, Joerg (Frontiers in Cardiovascular Medicine, 2022)
Obstructive Sleep Apnoea (OSA) is a common sleep-related breathing disorder,characterised by repeated interruptions in breathing while asleep due to collapse of the upper airway.OSA can have a significant impact on health and, when left untreated,is associated with increased risk of developing cardiovascular risks.Besides cardiorespiratory implications excessive daytime sleepiness, morning headaches, reduced memory and concentration are some further symptoms caused by OSA.CPAP therapy is the evidence-based treatment to maintain upper airway patency in patients with moderate to severe OSA.Proper adherence to CPAP therapy successfully abolishes nocturnal apnoeas and hypopnoeas, and diminishes consequences of uncontrolled OSA,such as treatment resistant hypertension.However,long term adherence to CPAP remains an unresolved limitation of this method.Although alternatives to CPAP therapy may be less efficacious,there is a variety of non-CPAP treatments available,that include conventional lifestyle advice, postural advice,the use of mandibular advancement devices,possible surgical treatments,such as uvulopalatopharyngoplasty,tonsillectomy,or maxillomandibular advancement,and the use of electrical stimulation of the upper airway dilator muscles,with hypoglossal nerve stimulation as an invasive and transcutaneous Electrical Stimulation (TESLA) as a non-invasive approach.For management of “difficult-to-treat” patients with OSA, particularly in those in whom first line therapy proved to be unsuccessful,a multidisciplinary team approach may be helpful.Symptom control and long-term cardiovascular outcomes may benefit from better adherence to the treatment,even at the cost of using a slightly less efficacious method than CPAP.Including patients in the successful management of their condition and advancing clinical trials in the field will help to resolve the relative lack of evidence for effective non-CPAP methods.